Marine data assimilation in the UK: the past, the present, and the vision for the future - Jozef Skákala; David Ford; Keith Haines; Amos Lawless; Matthew J. Martin; Philip Browne; Marcin Chrust; Stefano Ciavatta; Alison Fowler; Daniel Lea; Matthew Palmer; Andrea Rochner; et al. (Ocean Science, 2025)
In the last 2 decades, UK research institutes have led a wide range of developments in marine data assimilation (MDA), covering areas from operational applications in physics and biogeochemistry to fundamental theory. We highlight the emergence of strong collaboration in the UK MDA community over this period and the increasing unification of its tools. We focus on identifying the MDA stakeholder community and current/future areas of impact, as well as current trends and future opportunities. This includes the rapid growth of machine learning (ML)/artificial intelligence (AI) and digital-twin applications. We articulate a vision for the future, including the need for future types of observational data (whether planned missions or hypothetical) and how the community should respond to increases in computational power and new computer architectures (e.g. exascale computing). We contrast the requirements of different MDA areas, including physics, biogeochemistry, and coupled data assimilation (DA). Although the specifics of the vision depend on each area, common themes emerge. We advocate for balanced redistribution of new computational capability among increased model resolution, model complexity, more sophisticated DA algorithms, and uncertainty representation (e.g. ensembles). We also advocate for integrated approaches, such as strongly coupled DA (ocean–atmosphere, physics–biogeochemistry, and ocean–sea ice) and the use of ML/AI components (e.g. for multivariate increment balancing, bias correction, model emulation, observation re-gridding, or fusion).

A review of post-wildfire adaptations of surface-water-quality models: Synthesis, gaps, and opportunities - Zachary M. Shephard; Trevor F. Partridge; Sheila F. Murphy; Michelle A. Walvoord; Brian A. Ebel (Science of The Total Environment, 2025)

Impacts of a herring gull colony on runoff water quality from an urban green roof - Jinjie He; Elrod Owusu-Asumeng; Kate Zidar; Julian Stolper; Sudipti Attri; Jacob R. Price; Dustin Partridge; Franco Montalto; Christopher M. Sales (Science of The Total Environment, 2024)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

AAPS Perspective on the EURL Recommendation on the use of Non-Animal-Derived Antibodies - B. Gorovits; A. Hays; D. Jani; C. Jones; C. King; A. Lundequist; J. Mora; M. Partridge; D. Pathania; S. S. Ramaswamy; D. Rutwij; H. Shen; et al. (The AAPS Journal, 2021)

Future Distribution of Suitable Habitat for Pelagic Sharks in Australia Under Climate Change Models - Charlotte A. Birkmanis; Jennifer J. Freer; Leigh W. Simmons; Julian C. Partridge; Ana M. M. Sequeira (Frontiers in Marine Science, 2020)

Enhancing the Scientific Value of Industry Remotely Operated Vehicles (ROVs) in Our Oceans - Dianne L. McLean; Miles J. G. Parsons; Andrew R. Gates; Mark C. Benfield; Todd Bond; David J. Booth; Michael Bunce; Ashley M. Fowler; Euan S. Harvey; Peter I. Macreadie; Charitha B. Pattiaratchi; Sally Rouse; et al. (Frontiers in Marine Science, 2020)

Vamorolone, a dissociative steroidal compound, reduces collagen antibody-induced joint damage and inflammation when administered after disease onset - Jesse M. Damsker; Michaelyn R. Cornish; Priya Kanneboyina; Ila Kanneboyina; Qing Yu; Rachel Lipson; Aditi Phadke; Susan M. Knoblach; Karuna Panchapakesan; Melissa Morales; Alyson A. Fiorillo; Terence Partridge; et al. (Inflammation Research, 2019)

Gaze stabilization in mantis shrimp in response to angled stimuli - Ilse M. Daly; Martin J. How; Julian C. Partridge; Nicholas W. Roberts (Journal of Comparative Physiology A, 2019)

Application of Magnetic Resonance to Assess Lyophilized Drug Product Reconstitution - Thomas A. Partridge; Mahammad Ahmed; Sureshkumar B. Choudhary; Christopher F. van der Walle; Sajal M. Patel; Steven M. Bishop; Mick D. Mantle (Pharmaceutical Research, 2019)

Developing a Novel Model to Improve Research and care for Cancer Survivors: a Feasibility Study - Shoshana M. Rosenberg; Jennifer A. Ligibel; Jeffrey A. Meyerhardt; Eric D. Jacobsen; Judy E. Garber; Larissa Nekhlyudov; Craig A. Bunnell; Patricia Nutting; Kim Sprunck-Harrild; Sarah K. Walsh; Ann H. Partridge (Journal of Cancer Education, 2019)

Phototactic tails: Evolution and molecular basis of a novel sensory trait in sea snakes - Jenna M. Crowe‐Riddell; Bruno F. Simões; Julian C. Partridge; David M. Hunt; Steven Delean; Julian G. Schwerdt; James Breen; Alastair Ludington; David J. Gower; Kate L. Sanders (Molecular Ecology, 2019)
Dermal phototaxis has been reported in a few aquatic vertebrate lineages spanning fish, amphibians and reptiles. These taxa respond to light on the skin of their elongate hind‐bodies and tails by withdrawing under cover to avoid detection by predators. Here, we investigated tail phototaxis in sea snakes (Hydrophiinae), the only reptiles reported to exhibit this sensory behaviour. We conducted behavioural tests in 17 wild‐caught sea snakes of eight species by illuminating the dorsal surface of the tail and midbody skin using cold white, violet, blue, green and red light. Our results confirmed phototactic tail withdrawal in the previously studied Aipysurus laevis , revealed this trait for the first time in A. duboisii and A. tenuis , and suggested that tail photoreceptors have peak spectral sensitivities between blue and green light (457–514 nm). Based on these results, and an absence of photoresponses in five Aipysurus and Hydrophis species, we tentatively infer that tail phototaxis evolved in the ancestor of a clade of six Aipysurus species (comprising 10% of all sea snakes). Quantifying tail damage, we found that the probability of sustaining tail injuries was not influenced by tail phototactic ability in snakes. Gene profiling showed that transcriptomes of both tail skin and body skin lacked visual opsins but contained melanopsin ( opn4x ) in addition to key genes of the retinal regeneration and phototransduction cascades. This work suggests that a nonvisual photoreceptor (e.g., Gq rhabdomeric) signalling pathway underlies tail phototaxis, and provides candidate gene targets for future studies of this unusual sensory innovation in reptiles.

Considerations for bio-specimen collection among black women residing in the rural Deep South participating in a cancer prevention study - Tiffany L. Carson; Claudia M. Hardy; Eva Greene; Pamela L. Carter; Glenda James; Edward E. Partridge; Monica L. Baskin (Journal of Community Genetics, 2014)

Toxicity of sediment pore water in Puget Sound (Washington, USA): a review of spatial status and temporal trends - Edward R. Long; R. Scott Carr; James M. Biedenbach; Sandra Weakland; Valerie Partridge; Margaret Dutch (Environmental Monitoring and Assessment, 2013)

Predicting possible negative impacts of weed biocontrol by artificially suppressing invasive hawkweed in New Zealand’s tussock grasslands - Pauline Syrett; Guy J. Forrester; Helen M. Harman; Colin D. Meurk; Trevor R. Partridge; Lindsay A. Smith (BioControl, 2012)

Infection Control Measures to Prevent Invasive Mould Diseases in Hematopoietic Stem Cell Transplant Recipients - Kimberly Partridge-Hinckley; Gale M. Liddell; Nikolaos G. Almyroudis; Brahm H. Segal (Mycopathologia, 2009)

Factors affecting mark quality of alizarin complexone‐stained otoliths in juvenile black bream Acanthopagrus butcheri and a prescription for dosage - G. J. Partridge; G. I. Jenkins; R. G. Doupé; S. De Lestang; B. M. Ginbey; D. French (Journal of Fish Biology, 2009)
The relationships between otolith score, a function of increasing stain visibility, and the ratio of alizarin complexone (mg) to fish biomass (g) for 0·1, 0·6 and 7 g black bream Acanthopagrus butcheri show that acceptable marks are produced in all size classes using a stain‐to‐biomass ratio of 3·3 mg g −1 following an immersion period of 24 h.

Deep sea benthic bioluminescence at artificial food falls, 1,000–4,800 m depth, in the Porcupine Seabight and Abyssal Plain, North East Atlantic Ocean - E. J. V. Gillibrand; P. Bagley; A. Jamieson; P. J. Herring; J. C. Partridge; M. A. Collins; R. Milne; I. G. Priede (Marine Biology, 2007)

Vision and visual variation in the peacock blenny - E. M. White; D. M. GonÇalves; J. C. Partridge; R. F. Oliveira (Journal of Fish Biology, 2004)
Microspectrophotometry (MSP) revealed the presence of a rod and at least two cone classes (mid‐ and long‐wavelength sensitive) in the intertidal peacock blenny Salaria pavo . Both rhodopsin and porphyropsin based visual pigments were found in all fish, together with high individual variation in the chromophore ratio. The three morphs (females, males and sneaker males) differed in their spectral sensitivities (as measured with the optomotor response) with sneakers having higher sensitivity at long‐wavelengths than either males or females. This long‐wave displacement of peak sensitivity could be due to elevated proportions of porphyropsin visual pigments in the sneakers’ retinae. The lenses of all morphs exhibited a short‐wavelength cut‐off and an unusual layer of carotenoid was found behind the retinal pigment epithelium and in the outer segments of some cones. These screening pigments could serve a photo‐protective role or to improve visual contrast. No short‐wave photoreceptors were located using MSP. This indicates that this cone class may be absent or present at very low numbers in the retina. This is the first in depth study of the visual system of a blenniid fish and indicates potential within‐species visual variation that may be related to the species’ habitat and morph‐specific behavioural requirements.

Visual pigments and optical habitats of surfperch (Embiotocidae) in the California kelp forest - Cummings M.; Partridge J. (Journal of Comparative Physiology A, 2001)

Fossil pollen records of the problematical primitive angiosperm familyLactoridaceae in Australia - M. K. Macphail; A. D. Partridge; E. M. Truswell (Plant Systematics and Evolution, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

A late Holocene history of natural disturbance in lowland podocarp/hardwood forest, Hawke's Bay, New Zealand - Janet M. Wilmshurst; Matt S. McGlone; Trevor R. Partridge (New Zealand Journal of Botany, 1997)
Palaeoecological investigations of sediment cores from two lake basins in the Tutira and Putere districts of Hawke's Bay demonstrate the impact of volcanic activity, fires, and storms on the vegetation and soil stability before human settlement and deforestation. A “disturbance curve” derived from the classification and ordination of pollen records, and correlated with charcoal and sediment records, illustrates relative forest disturbance over time. Before anthropogenic forest clearance in Hawke's Bay, forest composition fluctuated frequently as a result of disturbance from fires, droughts, and a major volcanic eruption. Each natural disturbance, indicated by short‐term increases of seral taxa, was followed by complete forest redevelopment. Cyclonic storms were not a major cause of disturbance to lowland podocarp/hardwood forests in the region, nor to the bracken‐scrubland vegetation that replaced the forest after clearance. However, storms scoured and rapidly transported riverbank sediments into the lake basins. Compared with the preceding natural disturbances, deforestation by early Maori settlers represents a type and magnitude of disturbance previously unrecorded in the cores.